If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 12 = 6y + 14 Reorder the terms: 12 + 4y = 6y + 14 Reorder the terms: 12 + 4y = 14 + 6y Solving 12 + 4y = 14 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 12 + 4y + -6y = 14 + 6y + -6y Combine like terms: 4y + -6y = -2y 12 + -2y = 14 + 6y + -6y Combine like terms: 6y + -6y = 0 12 + -2y = 14 + 0 12 + -2y = 14 Add '-12' to each side of the equation. 12 + -12 + -2y = 14 + -12 Combine like terms: 12 + -12 = 0 0 + -2y = 14 + -12 -2y = 14 + -12 Combine like terms: 14 + -12 = 2 -2y = 2 Divide each side by '-2'. y = -1 Simplifying y = -1
| 12j=16j(j-8) | | (3w-4)(4w+6)= | | 3x-2(-5x+3)=72 | | 7+2(7)=30 | | h=0.5s-5 | | 20-5w=60 | | 6-10m=-54 | | 8-3p=-14 | | X+3y=-15 | | 2v^2-14v=0 | | 2+4n=-10 | | 1x-4x=6 | | 10=-5(3+w) | | 7-2n=5 | | 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 | | 9xy^2+4y-13=0 | | (x-3)=-3x+33 | | 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 | | (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) | | (-3xy)(7xy)= | | 14n+q=rt-4n |